Established anticoagulants in secondary haemostasis - Langer, E.; Ziemer, S. (Hämostaseologie, 2009)
In respect to the actual discussion of new anticoagulants in secondary haemostasis, we will give a short review on established oral anti -coagulation with vitamin K antagonists and parenteral anticoagulation by use of heparin. The different cumarin derivatives phenprocoumon, warfarin, and acenocoumarol are compared concerning to the management and influence of pharmacogenetic and pharmacokinetic factors. Studies to improve the safety of oral anticoagulation by vitamin K supplementation will be briefly discussed. The therapy with heparins include until now some problems of dose-response control. It is necessary to pay attention to contra-indications even for well known anticoagulants. Examples for that will be given.
Keywords: Vitamin K; vitamin K antagonists; unfractionated heparin; low-molecular-weight heparins